Chloride stress corrosion cracking of precipitation hardening S.S. impellers in centrifugal compressor. Laboratory investigations and corrective actions - Fantechi, F.; Innocenti, M. (Engineering failure analysis, 2001)
17-4 PH, precipitation hardening stainless steel (ASTM A 705 Grade 630), is widely employed in several industrial fields because of its favourable combination of excellent mechanical properties and good corrosion resistance. An important application of 17-4 PH is the construction of centrifugal compressor impellers, where performance benefits from the steel's high mechanical resistance even when it is necessary to limit hardness, for example, as per NACE MR0175, to avoid devastating sulphide stress cracking phenomena in sour environments. Nevertheless, there has been a case in which impellers made of 17-4 PH have been subject to failures. It was a centrifugal compressor employed in a gas lifting service in which the fluid entrained water with a high level of salinity. Laboratory failure analysis attributed the damage to chloride stress corrosion cracking phenomena and was followed by a study on the behaviour of 17-4 PH in chloride-rich environments and on the action to take to avoid damage causing forced outages and loss of production.